Short Communication: Flora and aves diversity in the Kasunanan Palace, Surakarta, Indonesia - IRFAN ABU NAZAR; SUNARTO SUNARTO; AHMAD DWI SETYAWAN; MUHAMMAD INDRAWAN; EDWI MAHAJOENO; WIDHI HIMAWAN; SOVIA WIJAYANTI; NUR CHOIRIYAH MERDEKAWATI; Diagal Wisnu Pamungkas; Haydar Ally; Daffa Nur Waskito; Ressa Karina; Asih Kinanti; Bisma Yoga Herdananta; SANGAJI SANGAJI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nazar IA, Sunarto, Setyawan AD, Indrawan M, Mahajoeno E, Himawan W, Wijayanti S, Merdekawati NC, Pamungkas DW, Ally H, Waskito DN, Karina R, Kinanti A, Herdananta BY, Sangaji. 2025. Short Communication: Flora and aves diversity in the Kasunanan Palace, Surakarta, Indonesia. Biodiversitas 26: 706-714. The development of Surakarta City, Central Java, Indonesia, as a MICE (Meeting, Incentive, Convention, and Exhibition) center poses challenges to the availability of land, which threatens green open spaces and their ecological functions. The Palace (Keraton), a cultural symbol of Surakarta, has the potential to provide green open space as the manifestation of its local wisdom. This research aimed to identify the diversity of flora and avian fauna that occurred in the Kasunanan Palace, Surakarta, Central Java, Indonesia. The study indicates that the Palace complex was still covered with medium to high vegetation cover, especially in the public open spaces of the Palace. Overall, the diversity index (H') of the flora reached 3.249, indicating a high level with an evenness index (E) of 0.624, indicating moderately even distribution. The most commonly found tree species were Hibiscus tiliaceus, Terminalia catappa, Mimusops elengi and Ficus benjamina. Fig tree (Ficus spp.) is a species with high symbolic and cultural value for the Palace. The avian diversity index (H') reached 2.084, indicating moderate diversity with an evenness index (E) of 0.328, indicating uneven distribution. The most commonly found avian species were Collocalia linchi, Passer montanus and Lonchura punctulata. These species are generalists, indicating high environmental pressure due to anthropogenic activities. The study results imply that green spaces in Keraton provide patches and stepping stones, which is an ideal habitat for developing urban biodiversity. This encourages greenspace restoration efforts based on the function of providing biodiversity through the conservation of special resources (large trees) and improving the quality of patches.